Genshin’s Ōjōyōshū and the Construction of Pure Land Discourse in Heian Japan - Rhodes, Robert F. (University of Hawaii Press, 2018)
According to the Ōjōyōshū, all of these are effective means for ensuring birth in Amida’s Pure Land.This impressively researched and updated treatment of the formative text in the Japanese Pure Land tradition will be welcomed by all scholars and students of Japanese religions. It also offers a fascinating window into Heian (794–1185) religious life, which will be of interest to anyone concerned with medieval Japan
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Jan 2018)
Keywords: Genshin -- 942-1017 -- Ōjō Yōshū; Pure Land Buddhism -- Doctrines; Amidismus